Epidemiology of Ehrlichiosis and Anaplasmosis among American Indians in the United States, 2000–2007 - Folkema, Arianne M. (The American Society of Tropical Medicine and Hygiene, 2012)
Ehrlichiosis and anaplasmosis infections among American Indians (AIs) have never been specifically examined, despite high rates of other tick-borne rickettsial diseases among AIs. The epidemiology of ehrlichiosis and anaplasmosis among AIs was analyzed using the National Electronic Telecommunications System for Surveillance (NETSS), Case Report Forms (CRFs), and Indian Health Service (IHS) inpatient and outpatient visits. The 2000–2007 average annual ehrlichiosis and anaplasmosis incidence among AIs reported to NETSS was almost 4-fold lower (4.0/1,000,000) than that using IHS data (14.9). American Indian cases reported from CRFs had a higher proportion of hospitalization (44%) compared with IHS (10%). American Indian incidence of ehrlichiosis and anaplasmosis was higher and showed a different age and geographical distribution than other races. These results highlight the need to improve collaboration between the ehrlichiosis and anaplasmosis surveillance systems for AIs so as to develop interventions that target the unique epidemiology and mitigate the burden of disease among this high-risk population.